HUBUNGAN ANTARA INTELEGENSI DENGAN RESILIENSI PADA MAHASISWA PSIKOLOGI SEMESTER PERTAMA UNIVERSITAS A - Clara Moningka (Universitas Bunda Mulia, 2013)
This research is aimed to find out the correlation between Intelligence Quotient (IQ) and resiliency in Psychology students on the first semester. This research is a correlational research, and using Pearson Product moment to calculate data. This study is based on the assumption of many previous studies, in which individuals with better intelligence will be easier to process the information that leads to the right decisions in their life. Intelligence itself is a multifaceted capacity, which includes learning new knowledge, logical thinking, good planning, problem solving, and adaptation to the situations or circumstances (Cohen & Swerdlik, 1999). Goddard (in Cohen & Swedlik, 1999) states that intelligence is the ability of an individual to be able to provide a solution to current problems and anticipate future circumstances. Therefore, the researcher wanted to find out if there is a correlation between the two variables. The result of Pearson product moment is .091 (r = .091, p = .59 ≥ .05), which means there is no correlation between intelligence with resilience. Keywords: Intelligence, resiliency, students